Sex and Region-Specific Differences in Microglial Morphology and Function Across Development - Indra R. Bishnoi; Evan A. Bordt (Neuroglia)
Microglia are exceptionally dynamic resident innate immune cells within the central nervous system, existing on a continuum of morphologies and functions throughout their lifespan. They play vital roles in response to injuries and infections, clearing cellular debris, and maintaining neural homeostasis throughout development. Emerging research suggests that microglia are strongly influenced by biological factors, including sex, developmental stage, and their local environment. This review synthesizes findings on sex differences in microglial morphology and function in key brain regions, including the frontal cortex, hippocampus, amygdala, hypothalamus, basal ganglia, and cerebellum, across the lifespan. Where available, we examine how gonadal hormones influence these microglial characteristics. Additionally, we highlight the limitations of relying solely on morphology to infer function and underscore the need for comprehensive, multimodal approaches to guide future research. Ultimately, this review aims to advance the dialogue on these spatiotemporally heterogeneous cells and their implications for sex differences in brain function and vulnerability to neurological and psychiatric disorders.